Analisis Pengaruh Struktur Kepemilikan Manajemen, Kebijakan Hutang Dan Risiko Terhadap Kinerja Keuangan Perusahaan Industri Manufaktur Tbk Di Indonesia - Harryono, Sumadji; noerchoidah, noerchoidah (Majalah Ekonomi, 2017)
The main objective of this study was to examine the effect of ownership structure management, debt policy and the risks to the value of public manufacturing companies in Indonesia.. Unlike the agency problems in capital markets have developed, agency problem in Indonesia is the difference between the interests of the minority owners of the majority owner. The hypothesis in this study were: (1) ownership structure, significant effect on debt policy, (2) ownership structure and debt policies have a significant effect on the financial performance of the company. This study wanted to test the agency theory, Jensen and Meckling (1976), Pecking Order Theory, Myers (1984), The trade off models and Signaling Theory, Copeland (1992). The population in this study is an open manufacturing company listed on the Indonesia Stock Exchange. A total of 157 companies were taken as samples by using purposive sampling. Data were analyzed using the Structural Equation Modelling. These studies suggest that the ownership structure of management, significant effect on debt policy. Ownership structure and debt policies have a significant effect on the financial performance of the company. Results of this study do not support the agency theory, Jensen and Meckling (1976) but the results of this study support the Pecking Order Theory, Myers (1984), The trade off models and Signaling theory, Barcley (1995).